Is There Really a Child Penalty in the Long Run? New Evidence from IVF Treatments - Petter Lundborg; Erik Plug; Astrid Würtz Rasmussen (Institute of Labor Economics (IZA), 2024)
Newly matched data on in vitro fertilization (IVF) treatments are used to estimate the long-run consequences of children on the labor market earnings of women and men (often referred to as child penalties). We measure long-run child penalties in IVF-treated families by comparing the earnings of successfully and unsuccessfully first-time treated women and men up to 25 years after the first IVF treatment. In the short run, we find a large penalty immediately after the birth of the first child. In the long run, however, we find that the child penalty fades out, disappears completely after 10 years, and even turns into a child premium after 15 years, offsetting the initial setbacks experienced when children are young. Our findings therefore challenge the widely held view that children are the primary drivers behind the long-run gender gap in earnings.
Keywords: J13; J16; J31; 330; child penalty; gender earnings gap; fertility